Effects of Chronic Stress and Alendronate Therapy on the Osseointegration of Titanium Implants - Conte Neto, Nicolau; de Andrade, Cleverton Roberto; Spolidorio, Luis Carlos; Planeta, Cleopatra da Silva [UNESP]; Cruz, Fábio Cardoso; de Souza Bastos, Alliny; Marcantonio, Elcio (Wiley, 2013)
Purposes: The purposes of this study were to evaluate the influence of chronic stress (CS) on implant osseointegration and also to analyze whether alendronate (ALN) therapy could prevent these eventual stress-negative effects. Materials and Methods: Adult male Holtzmann rats were assigned to one of the four experimental groups: AL (ALN; 1mg/kg/week; n=12), ALS (ALN+CS; 1mg/kg/week; n=12), CTL (sterile physiological saline; n=12), or CTLS (sterile physiological saline+CS; n=12). After 58 days of drug therapy, the ALS and CTLS groups were exposed to CS, and 2 days later all animals underwent tibial implant installation. The animals were euthanized 28 days following the operative surgical procedure. Results: It was observed that the CTLS group presented an impairment of bone metabolism represented by lowest levels of bone-specific alkaline phosphatase and bone area fraction occupancy values. Furthermore, these animals presented a higher proportion of empty osteocytic lacunae. In contrast, the ALN therapy showed increased osseointegration and torque value parameters, regardless of stress exposition. Conclusions: Analysis of the data presented suggests that CS partially impairs the osseointegration of tibial implants and that ALN therapy is able to prevent these negative effects. © 2013 Wiley Periodicals, Inc.
Keywords: Alendronate; Bone; Operative surgical procedure; Osseointegration